2020
DOI: 10.1002/oby.22761
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd Ameliorates High Fat Diet‐Induced Obesity by Enhancing Adaptive Thermogenesis in a cAMP‐Dependent Manner

Abstract: Objective With the discovery of thermogenic adipocytes in humans, it has been hypothesized that enhancing adaptive thermogenesis may improve obesity. Although many studies have found that ginseng can improve obesity, the beneficial effects of ginsenoside Rd on obesity and its mechanisms have not been studied. Methods High‐fat diet‐induced obese mice were used as the study subjects, with intraperitoneal injection of Rd daily at a dose of 15 mg/kg. Body weight and energy metabolism were observed. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In this study, TAC, CAL and ISO-induced HF mice models were performed to simulate clinical symptoms of HF [ 28 , 29 ]. Ginsenoside Rd has been studied to reduce insulin resistance and alleviate TAC-induced cardiac hypertrophy [ 30 , 31 ]. In the present study, ginsenoside Rd was found to ameliorate myocardial ischemia injury in TAC, CAL and ISO-induced HF, mainly due to enhancing myocardial contractility and inhibiting cardiac pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, TAC, CAL and ISO-induced HF mice models were performed to simulate clinical symptoms of HF [ 28 , 29 ]. Ginsenoside Rd has been studied to reduce insulin resistance and alleviate TAC-induced cardiac hypertrophy [ 30 , 31 ]. In the present study, ginsenoside Rd was found to ameliorate myocardial ischemia injury in TAC, CAL and ISO-induced HF, mainly due to enhancing myocardial contractility and inhibiting cardiac pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…The browning of white adipose tissue induced by cold stress and cAMP levels are increased by ginsenoside Rd. In particular, Rd alleviates obesity and insulin resistance by upregulating thermogenesis through the cAMP/protein kinase A (PKA) signaling pathway ( Yao et al, 2020 ). In fast-food diet-induced non-alcoholic fatty liver disease (NAFLD), fermented ginsenoside Rd with Cordyceps militaris regulates lipid metabolism and the inflammatory response via mTORC1 signaling ( Choi et al, 2019 ).…”
Section: Ginsenoside Rd Targets Multiple Diseasesmentioning
confidence: 99%
“…In addition, other studies have found that ginsenosides Rb2, Rg1, and Rg3 induced AMPK phosphorylation, stimulated the expression of UCP1, and increased thermogenesis and mitochondrial gene expression to induce BAT activation and white adipocyte browning Hong et al, 2019;Kim et al, 2020). Ginsenoside Rd enhances thermal gene expression in brown adipose tissue through the PKA signaling pathway and increases browning of white adipose tissue induced by cold exposure (Yao et al, 2020).…”
Section: Effects On Body Energy Consumption Promote White Adipose Tismentioning
confidence: 99%